To "B" or Not to "B" : A Welfare Analysis of Breaking Up Monopolies in an Endogenous Growth Model - Xie, Danyang (IMF Working Papers; Working Paper ;, 2000)
This paper studies the welfare consequences of a government regulation that forces a patented equipment to be supplied by a number of independent producers. On the one hand, such a regulation hurts the value of a patent and therefore reduces activities in the R and D sector. On the other hand, the enhanced competition for the equipment improves efficiency in the manufacturing sector. Should monopolies protected by intellectual property rights be broken up? The answer is 'no' in a Romer-type growth model, but there is sufficient reason to believe that the answer could be 'yes' in a model advocated by Jones (1995).